Analisis Sentimen Dampak Covid-19 Terhadap Pembatalan Keberangkatan Ibadah Haji Pada Tahun 2020 - Kartika, Mila; Saepudin, Sudin; Gustian, Dudih (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The government through the Ministry of Religious Affairs canceled the departure of pilgrims from Indonesia in 2020. The decision was taken, considering the Covid-19 pandemic still plagues almost all parts of the world, including Indonesia and Saudi Arabia.